Leslie Martin and the formal order - Ferrer Fores, Jaime J. (Cuadernos de Proyectos Arquitectónicos, 2016)
Abstract This paper analyzes the architecture of Sir Leslie Martin (1908-2000) and covers the intense professional career that starts with the Nursery School at Northwich, Cheshire (1937-1938) or the Alastair Morton house at Brampton (1938) which are ascribed to the orthodoxy of modern architecture, and continues with the projects he planned as the architect responsible of the railway company for stations and railroad infrastructure rearrangements in the postwar, interventions that will prepare him for his architectural maturity stage which he crystallizes in buildings for the Royal Festival Hall in London (1948-1951), the Harvey Court, Cambridge (1958-1962), the auditoriums for the Middleton Hall, University of Hull (1958 ), the School of Music (1974) and College (1979) at Cambridge University and his proposal for the University of Bristol (1979) that illustrate the essential basis of his coherent architectural career where the tradition of modern architecture, the spatial continuity and the formal order converge. This analysis of the works in the fifties, sixties and seventies illustrates the architect’s constants through the chronological exploration of his works that reveal the compositional mechanisms, the search for formal order and the correct spatial organization taking into account the functional requirements, the relationship with the site and the technological resources that determine his entire career which is characterized by formal consistency and architectural coherence.